Abuse and its association with depression among elderly people (Bangladesh Journal of Psychiatry, 2021)
Abuse is an unacceptable incident that has harmful effects on the physical and mental health of the elderly. Depression is one of the most neglected psychological conditions though very common among elderly people, the rate of which is high among the abused ones. In an attempt to evaluate the status of depression among the elderly people who experience abuse, this cross-sectional study interviewed 175 elderly people living in an urban setting from 1 January 2019 to 31 December 2019. The results showed that, respondents who experienced abuse were 33.7% and respondents with depression were 53.1%. It has been observed that, among the respondents who experienced abuse, 81.3% of them were suffering from depression, where 33.9% had mild levels of depression, 16.9% had a moderate level of depression and 30.5% had a severe level of depression. The mean score of depression was significantly higher among the abused group of respondents (8.6±3.9) than the not abused group of respondents (4.4±3.6) (p